“Casualties of War”: The Japanese Occupation of Korea and Its Impact on Mothers and Daughters in Yoko Kawashima Watkins’ So Far from the Bamboo Grove and Sook Nyul Choi’s Year of Impossible Goodbyes - Halko, Gabrielle Atwood (SARE: Southeast Asian Review of English, 2018)
World War II is only partially represented in American history and culture, with the Japanese occupation of Korea rarely acknowledged. An analysis of two middle-grade novels, Yoko Kawashima Watkins’ So Far from the Bamboo Grove and Sook Nyul Choi’s Year of Impossible Goodbyes, illuminates three underrepresented issues: conflicting portrayals of the occupation of Korea in two popular children’s texts, the influence of American readers on those narratives, and the ways in which the constructs of stereotypical mothers and daughters are impossible to sustain during wartime.